‘There is no me, there is only us’: The erasmus bubble as a transient form of transnational collectivity - Cairns, D.; Cuzzocrea, V.; Ewa Krzaklewska (Forms of collective engagement in youth transitions: A global perspective, 2021)
I came alone. I did not know what to expect. But I knew someone was waiting for me. Then I found out what it was. A family. Not just a normal family. Brothers and sisters from all over the world, wait-ing for me on this island that I learned to call home. And will con-tinue to be home, even after I leave. Because home is where heart is. Never forget that. Never.